2016
DOI: 10.1590/1516-3180.2015.01733009
|View full text |Cite
|
Sign up to set email alerts
|

Self-administered versus interview-based questionnaires among patients with intermittent claudication: Do they give different results? A cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Many clinical investigations use generic and/or specific questionnaires to obtain information about participants and patients. There is disagreement about whether the administration method can affect the results. The aim here was to determine whether, among patients with intermittent claudication (IC), there are differences in the Walking Impairment Questionnaire (WIQ) and European Quality of Life-5 Dimension (EQ-5D) scores with regard to: 1) the questionnaire administration method (self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
10
0
4
Order By: Relevance
“…Second, the study used convenient and snowball sampling to recruit participants, and thus the results may not be generalizable to all students of healthcare and non-healthcare sectors. Third, an online self-administered questionnaire form was used instead of a face-to-face interview, with potential bias in reporting; however, studies in the health field have shown that there may not be a difference between a self-administered and interviewer-administered questionnaire ( 43 , 44 ). The reasons for the refusal or low willingness to receive COVID-19 vaccines need further investigation, possibly using qualitative or mixed methods approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the study used convenient and snowball sampling to recruit participants, and thus the results may not be generalizable to all students of healthcare and non-healthcare sectors. Third, an online self-administered questionnaire form was used instead of a face-to-face interview, with potential bias in reporting; however, studies in the health field have shown that there may not be a difference between a self-administered and interviewer-administered questionnaire ( 43 , 44 ). The reasons for the refusal or low willingness to receive COVID-19 vaccines need further investigation, possibly using qualitative or mixed methods approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Self-administered instruments are cost-effective and efficient, but may bring about respondent bias, whereas interviewer-administered instruments, while able to ensure high response rates, are always resource-intensive and expensive to administer. 73 Although the literature showed that there was no significant difference in scores outcome between these two administration modes, 74 75 the relevant studies mostly concerned health-related quality of life instruments. It is still unknown whether the same is true for health literacy instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was pre-tested on 15 respondents and adjustments were made to the unclear items accordingly (Hilton, 2017). The questionnaires were completed with the face-to-face assistance of the interviewer and reckon that this approach this improves the quality of the information collected (Lozano et al, 2016). Following Leahy (2004), the data was recorded on a spreadsheet and later analysed through the use of Microsoft Excel function for plotting graphs.…”
Section: Competitionmentioning
confidence: 99%